Teoria da eficácia ultraterritorial das normas coletivas de trabalho - Supioni Junior, Claudimir (2017)
This research reports findings resulted in a theoretical model, aiming to describe and systemizing the efficacy of collective labor standards of Brazilian territorial scope. The research problem is represented by the following question: Would collective bargaining instruments be capable of producing effects on a geographic area broader than the territorial base of the document’s signatory unions, to the extent of also considering the labour occurred in another locality? Owing to a gap in literature on the subject, similar concepts were adopted from other branches of the legal science. The theoretical rationale was derived from the richness of the Private International Law’s literacy, for presenting the necessary postulations for object’s confrontation. The research method comprised of commencing from hypothesis or conjecture, inferring its consequences, applying tests of falsifiability and, at the end, support or refute hypothesis or initial conjecture. Such method allowed to validate several premises that converged into three central postulates, that altogether built the foundation of the presented thesis: (i) the individual contract of employment is not necessarily ruled by the conventional norms celebrated by the union, whose territorial base lies in the place the worker performs his professional activities; (ii) the employment relationship is ruled by collective norms whereby a closer bond exists, in accordance with the principle of proximity; (iii) it is possible that different aspects of labour contract may connect with different collective norms, as they have a closer interconnection amongst them, as per the deduction’s method guides. Despite indeterminacy caused by the proximity’s principle, this research advanced forward and investigated assumptions of closer bonds, clearly constructed hypothetically and aprioristically, formulating then an application model synthesized in the sequence of statements presented in its concluding chapter